Promotion of human rights & social justice for persons with disabilities by religious means: The role and contribution of zakat in Malaysia - Mokhtar, Khairil Azmin; Md Tah, Ikmal Hisham (2016)
State Parties have duty to ensure promoting full realization of human rights for PWD through appropriate legislative, administrative and other measures including maximum available resources with regard to socio-economic development. Malaysia has become the party to the CRPD and domestic legislation have been passed by the government to promote and protect the PWD. One of the Quran’s major themes is social justice. Islam builds its community out of human obligation toward each other, making each Muslim accountable for the well-being of every other Muslim. Zakat promotes care and love between each other in the community by guaranteeing justice unto the least of them, while shielding the weak from injury. It enshrines the right of help for the community’s needy, and in doing so it builds a relationship of consideration and appreciation between society’s members. Zakat awakens the individual’s social spirit with the truest practical expression of brotherhood. It links one to others by a sense of personal responsibility and it binds everyone to the individual through an obligation of sufficiency. In Malaysia, the role of zakat (tithe) institution in assisting those who are poor and needy within the beneficiaries (asnaf) that allows under the Shariah is crucial to achieve social justice. The institution has become integral part within Malaysian Muslim society where government has set up proper mechanism of paying zakat through institution recognized under the law. Zakat institution would help to improve the living condition of PWD not just in terms of eradicating poverty among them but also improving their life and getting support system. This article will address the importance of zakat institution in Malaysia to assist PWD who is in dire need for financial and support system that allows them to participate meaningfully within community in line with the spirit of CRPD and local laws.